Effect Of Educational Changes In Pregnant Women Physiological Changes Towards Pregnant Women Anxiety - Husnawati; Fitriani; Asri (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2020)
Health education regarding pregnant women anxiety will provide more understanding to pregnant women as well as to prevent stress. The phenomenon of the problem at Bonto Bangun Puskesmas is that health education is carried out in the class of pregnant women, but not all pregnant women participate in the program. The aim of the study was to determine the effect of physiological change education in pregnant women on the anxiety level of pregnant women at Bonto Bangun Community Health Center. This study used a pre-experimental design by means of a One-shot case study. The number of samples is 5 people, sampling technique with purposive sampling. The research was conducted at the Bontobangun Community Health Center in August 2020. The results showed that the level of anxiety of pregnant women before education was the highest moderate anxiety compared to no anxiety, mild and severe anxiety. Meanwhile, the level of anxiety of pregnant women after being given education decreased, namely mild anxiety was higher than moderate anxiety and there was no anxiety. After testing the analysis using SPSS, namely the marginal homogeneity test, the p-value was 0.000 <Î± value of 0.05. This means that there is a significant correlation between the two variables. Conclusions and suggestions: There is an effect of physiological change education of pregnant women on the level of anxiety of pregnant women at Bontobangun Community Health Center. It is hoped that education on physiological changes will become a reference for pregnant women classes or other programs.